Learning difficulties among primary school students 6,5,4 - ئافان عبدالله حسن; شةوبة عبدالله ملا طاهر; عمر ياسين جباري (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
This study aims to determine the prevalence of learning disabilities among 4-6 grades of elementary schools. The study sample consists of (307) students from (27) schools which is equivalent to (8%) of the research population (3832) students in the basic stage in Sulaymaniyah governorate. The survey tool consists of (60) items divided into seven main areas defined by Interagency Committee of Learning Disabilities in 1987. The areas are calculations, reading, writing, thinking, listening, verbal expression and spelling. The survey response scale consists of (always, often, sometimes, rarely, never) with (1,2,3,4,5) values. The Statistical are performed to derive the psychometric properties of the scale. The study concludes with: Students were identified by taking in consideration a diagnostic criterion for learning disabilities and a tool to identifying students with learning disabilities. The results of a survey find the incidence of learning disabilities are high, it reached (21%), and The prevalence of learning difficulties among males were more susceptible to learning difficulties than females. At the end of the research a number of suqqetions and recommendations were provided.